Role of RUNX2 transcription factor in epithelial mesenchymal transition in non-small cell lung cancer lung cancer: Epigenetic control of the RUNX2 P1 promoter (2019)
Lung cancer has a high mortality rate in men and women worldwide. Approximately 15% of diagnosed patients with this type of cancer do not exceed the 5-year survival rate. Unfortunately, diagnosis is established in advanced stages, where other tissues or organs can be affected. In recent years, lineage-specific transcription factors have been associated with a variety of cancers. One such transcription factor possibly regulating cancer is RUNX2, the master gene of early and late osteogenesis. In thyroid and prostate cancer, it has been reported that RUNX2 regulates expression of genes important in tumor cell migration and invasion. In this study, we report on RUNX2/p57 overexpression in 16 patients with primary non-small cell lung cancer and/or metastatic lung cancer associated with H3K27Ac at P1 gene promoter region. In some patients, H3K4Me3 enrichment was also detected, in addition to WDR5, MLL2, MLL4, and UTX enzyme recruitment, members of the COMPASS-LIKE complex. Moreover, transforming growth factor-? induced RUNX2/p57 overexpression and specific RUNX2 knockdown supported a role for RUNX2 in epithelial mesenchymal transition, which was demonstrated through loss of function assays in adenocarcinoma A549 lung cancer cell line. Furthermore, RUNX2 increased expression of epithelial mesenchymal transition genes VIMENTIN, TWIST1, and SNAIL1, which reflected increased migratory capacity in lung adenocarcinoma cells. © The Author(s) 2019.